Effects of fermented soybean meal substitution for fish meal on intestinal flora and intestinal health in pearl gentian grouper - Pang, Aobo; Peng, Cong; Xie, Ruitao; Wang, Zhuoduo; Tan, Beiping; Wang, Tingting; Zhang, Wei (Frontiers in Physiology, 2023)
This study explored the role of replacing fish meal protein with fermented soybean meal (FSBM) protein on the growth performance and intestinal morphology, immunity, and microbiota of the pearl gentian grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂). Three isonitrogenous and isolipidic diets with increasing levels of FSBM (0%, 20% and 40%; referred to as FM, FSBM20 and FSBM40 diets, respectively) as a replacement for fish meal were selected for this study. The pearl gentian grouper were fed these diets for 10 weeks. The findings revealed that the growth of fish fed the FSBM diets (FSBM20 and FSBM40) were remarkably lower than the fish fed the FM diet. Pathological manifestations of intestinal inflammation, such as shortened intestinal mucosal folds and thickened lamina propria, were observed in the fish fed the FSBM diets. Moreover, the gene expression levels of IL1β, IL12, IL17, and TNFα were remarkably up-regulated in fish fed the FSBM40 diet, in contrast to the gene expression levels of IL4, IL5, IL10, and TGFβ1, which were remarkably down-regulated. The FSBM diets significantly affected the stability of the fish gut microbiota. Photobacterium was the dominant phylum in all experimental groups, and the proportion of these bacteria gradually decreased with increasing FSBM substitution. The composition of intestinal flora at the genus level was not the same in the three experimental groups, with a richer composition of intestinal bacteria detected in the FSBM20 and FSBM40 groups. The correlation between intestinal flora balance and immune gene expression revealed that only Photobacterium was negatively correlated with the above up-regulated genes, while other bacteria were positively correlated with these pro-inflammatory factors. Photobacterium was positively correlated with the above down-regulated genes, while other bacteria were negatively correlated with these anti-inflammatory factors. In conclusion, high levels of substitution of FSBM for fish meal causes intestinal inflammation in pearl gentian grouper. This is likely associated with changes to the intestinal flora. More attention should be paid to the negative role of dietary FSBM on intestinal flora.